Improved cassava for inland valley agroecosystems - Ekanayake, I.J.; Dixon, A.; Asiedu, Robert; Izac, A.M.N. (1994)
A substantial impact on Africa agriculture can be made through research on crop improvement for the extensive inland valley agro-ecosystems (IVS) extending from the humid forest to the savanna zones in sub saharan Africa. Systematic surveys of farmers have shown that cassava is a favoured upland crop for the IVS. Screening of cassava for IVS adaptation in the sub Saharan Africa is a continued activity at IITA. Preliminary results indicate that elite clones TMS 85/00025 (15.9t/ha), TMS 63397 (13.3 t/ha) and TMS 84/00003 (12.6 t/ha) superceded the yield levels of local checks during a 6 month growing period. A scheme for the improvement of cassava targeted for IVS is described. In addition, for cassava and other upland crops to be suitable crop components in this highly fragile agro-ecosystem, attention has to be given to a combination of improved genotypes with appropriate water control, weed control and fertility management. Research at IITA to date has attempted to address these short and long term production constraints.